Molecular Detection of Beta-Lactamase Genes (KPC and CTX-M) of Pseudomonas aeruginosa in Diabetic Foot Ulcers Patients - Almashhady, Fatima Radawi; Abd Al-Ameer, Sama S.; Al-aaraji, Hashim Mohammed Hashim; Abbas, Khitam F. (Medical Science Journal for Advance Research, 2024)
Background: Diabetic foot ulcers (DFUs ) are an inflammatory disease caused by a bacterial infection such as Pseudomonas aeruginosa (P. aeruginosa), provided with genetic virulence factors. This study aims to detect KPC and CTX-M genes of P. aeruginosa isolated from chronic DFU patients. Methods: One hundred twenty DFU patients were recruited from Al-Sader Medical City and Al-Hakim General Hospital in Najaf province from September to January 2021 to collect ear swaps. The Primary identification depends on Gram stain and biochemical tests. We also used the Vitek 2 system to make another identification and examine resistance to antibiotics. A polymerase chain reaction (PCR) was used to amplify the required genes. Furthermore, gel electrophoresis was performed to show the amplified genes. Results: The results have revealed that 100 samples (83.3%) give a positive outcome, while 20 samples (16.6%)are negative for culture bacteria. Only 17(17 %) of the 100 clinical specimens showed positive tests for P. aeruginosa. However, the gene, CTX-M gene is found in 58.8% of P. aeruginosa isolates, while the KPC gene is not found in the isolates. Conclusion: Our findings suggest that P. aeruginosa is one of the most common causes of DFU infection in Iraqi patients and The levels of MDR of P. aeruginosa isolates in Najaf hospitals were undoubtedly high. Most bacterial isolates show the presence of the CTX-M gene. The presence of these genes is one of the virulence factors and probably partly explains the resistance to antibiotics.